Políticas redistributivas e a redução das desigualdades: a contribuição potencial dos consórcios intermunicipais - Souza, Patrícia Laczynski de (2012)
This piece of work aims to answer the two following questions: are consortia regional arrangements capable of carrying out policies to fight inequality? Are consortia capable of thinking inter-municipal governance from the redistribution context? Considering that Brazil is one of the most unequal countries, the study sought to deepen the practical debate about inequality and search for ways - from sub-regions - to implement redistributive policies. The inequality discussed here approaches different dimensions considering not only the income perspective, but also the access to public services (health, education, housing), the inequality between municipalities (size, resources, population) and the geographical one. The redistributive policies are based on the work of the North American author Theodore Lowi, who created a model to distinguish distributive, regulatory and redistributive public policies based on the impact in the society and on the spaces for negotiation of conflicts. Experiences of redistributive policies applied to the actual Brazilian context are also discussed. Respecting the fact that the Federal Government has an important role in the implementation of redistributive policies, this piece of work has attempted, nevertheless, to comprehend the role of local governments in the reduction of inequalities. The object of analysis of this research are inter-municipal consortia, ‘organisations resulting from the willingness of significant political actors of different municipalities (mayors) to cooperate aiming to solve problems related to a specific thematic or sector’ (CALDAS, 2008). Brazilian consortia are arrangements for local and regional management and inter-municipal cooperation which have become institutionalised before the creation of a specific legislation (Law 11.107/05), characterising an inter-organisational structure that had already been consolidated. The methodology chosen was the study of four consortia in the field of development and health. The choice for these fields of action is justified by the fact that development is widely debated as a path to reduce poverty and health is the most advanced field of debate around equity in Brazil. The Vale do Paranapanema Inter-municipal Consortium (CIVAP) and the Vale do Ribeira Inter-municipal Consortium (CODIVAR) are both located in the State of São Paulo, were both created in 1980 and are among the first development consortia encouraged by the then-State Governor André Franco Montoro (1983-1986). The Production and Supply Intermunicipal Consortium (CINPRA) is located in the State of Maranhão, near the state capital. Created in 1997, it aims to stimulate the regional development from small rural producers. The Alto São Francisco Health Inter-municipal Consortium (CISASF) is the first inter- municipal consortium for health created in the State of Minas Gerais (in 1983) and seeks to decentralise and increase the services of specialised healthcare. One concludes that consortia are tools that empower municipalities to increase the access of the population to public services and, as a result, to improve the life quality of people with more equity and are also capable of implementing quasi-redistributive policies, once that their actions benefit a large group of society, but their costs are not originated from another specific social group, but from an entire region. Finally, one should complement that consortia will only consider this inter-municipal governance from a perspective of maturity of mayors and technicians involved in consortia, process that should be induced by federal or state governments.